Comparison of knowledge of mothers with stunted and severely stunted toddlers before and after education with brainstorming and audiovisual methods - Kemalaa, Roosi Rachma; Sanjaya, Ayling (Gaceta Médica de Caracas, 2022)
Introduction: Stunting is the incidence of malnutrition, especially in toddlers, that lasts a long time. Stunting has several impacts, including an increased risk of morbidity in the form of an increased risk of occurrence and mortality that the incidence of infection can cause. This study used brainstorming and audiovisual methods to compare the knowledge of mothers who had stunted and severely stunted toddlers before and after being given a video.